The impact of farm input subsidies on economic efficiency of maize production in Malawi - Chiromo, John (Graduate School of Business, 2018)
The study analyzed the impact of the farm input subsidy programme (FISP) on the technical, allocative and economic efficiency and determining factors associated with these efficiencies of 12, 271 smallholder maize farmers from 2010 IHS3 dataset in Malawi. Descriptive statistics, stochastic frontier approach as and a Cobb-Douglas production function were applied. Yield responsiveness to production inputs was estimated by computing input elasticities. The findings indicate that technical efficiency of smallholder maize farmers ranged from 15.7 to 78.9 with a mean of 61.3 percent reflecting a substantial level of inefficiency. The allocative efficiency scores were between 23.5 and 86.2 with a mean of 66.9 percent reflecting a substantial level of allocative inefficiency. The economic efficiency scores were between 14.1 and 74.6 with amean of 59.2 percent reflecting a substantial economical inefficiency. An estimated return to scale was 0.87 indicating that during the period under review, smallholder maize farming decreased by about 13 percent. The results of second stage Tobit regression estimations indicates that the FISP programme improved the efficiencies of maize farmers in Malawi. In addition, t farmers’ age, farming experience, education years, having an income generating activity and receiving remittance were also identified as significant drivers of production capacity of smallholder farmers maize. However, farmers’ marital status, family size and distance to the market had a negative impact on smallholder farmers’ capacity in maize production. Smallholder farmers in Malawi were experiencing a decreased return to scale meaning that they were technical, allocative and economically inefficient in maize production. From the findings, among other issues to be considered for the improvement of technical, allocative and economic efficiencies of maize production among smallholders farmers, the government should support only energetic farmers, make farm inputs available and accessible to farmers, continued advocacy on v adoption of family planning to reduce population growth to carter for scarcity of resources, increase and enhance extension services to help in educating these smallholder farmers in handling new technologies associated with modern agriculture, encourage them to engage in IGAs to complement FISP in purchasing farm inputs, increased and extended cash transfer program to economically empower these smallholder farmers.